Karakteristik Teori Produksi Dalam Islam Berbasis Maqosid Syariah: Suatu Formulasi Konseptual - Weni Aulia Ramadhani; Muhammad Farrel; Dina Anggita Sari; M. Yusuf Bahtiar (Indo Publishing, 2026)
Production is a fundamental activity in the economic system because it determines the availability of goods and services needed by society. In conventional economics, production activities are generally oriented toward efficiency and profit maximization. However, this approach often overlooks ethical dimensions, social responsibility, and sustainability. In addition, studies that specifically integrate production theory in Islamic economics with the framework of maqasid sharia remain relatively limited in contemporary Islamic economic literature. Therefore, this study aims to analyze the concept of production in Islamic economics based on maqasid sharia. This research employs a qualitative approach using a literature review method by analyzing various scientific journals and relevant academic literature published within the last ten years concerning production theory in Islamic economics and the concept of maqasid sharia. The results show that the concept of production in Islamic economics does not merely emphasize economic efficiency but also integrates moral values, social justice, and public welfare. The principles of maqasid sharia, which include the protection of religion, life, intellect, lineage, and wealth, can serve as a normative framework in directing production activities to become more equitable and sustainable. This study contributes conceptually by emphasizing the importance of integrating production theory and maqasid sharia as a foundation for developing a production model oriented toward social welfare in Islamic economics.